2020
DOI: 10.1101/2020.09.15.297739
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The piRNA pathway sustains adult neurogenesis by reducing protein synthesis and cellular senescence

Abstract: In specific niches of the adult mammalian brain, neural progenitor cells (aNPCs) ensure lifelong neurogenesis. Proper regulation of this process entails important implications for brain plasticity and health. We report that Piwil2 (Mili) and PIWI-interacting RNAs (piRNAs) are abundantly expressed in aNPCs but depleted in their progeny in the adult mouse hippocampus. Loss of function of the piRNA pathway in aNPCs inhibited neurogenesis and increased reactive gliogenesis in vivo and in vitro. PiRNA pathway deple… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 76 publications
3
2
0
Order By: Relevance
“…In the current study, PIWIL2 expression was not detected in sALS postmortem samples, supporting the observation by Gasparini et al [25]that PIWIL2 is expressed in neural stem/ progenitor cells, but not in neurons. PIWIL3 also was not detected by immunoblotting in these samples, while PIWIL4 was downregulated by 0.5-0.6-fold in most sALS samples.…”
Section: Piwi Protein Dysregulation As a Potential Cause Of Alssupporting
confidence: 92%
“…In the current study, PIWIL2 expression was not detected in sALS postmortem samples, supporting the observation by Gasparini et al [25]that PIWIL2 is expressed in neural stem/ progenitor cells, but not in neurons. PIWIL3 also was not detected by immunoblotting in these samples, while PIWIL4 was downregulated by 0.5-0.6-fold in most sALS samples.…”
Section: Piwi Protein Dysregulation As a Potential Cause Of Alssupporting
confidence: 92%
“…In the current study, PIWIL2 expression was not detected in sALS postmortem samples, supporting the observation by Gasparini et al [26], that PIWIL2 is expressed in neural stem/progenitor cells, but not in neurons. PIWIL3 also was not detected by immunoblotting in these samples, while PIWIL4 was downregulated by 0.5-0.6-fold in most sALS samples.…”
Section: Piwi Protein Dysregulation As a Potential Cause Of Alssupporting
confidence: 92%
“…Interestingly, the hippocampus shows the highest number of unique piRNA sequences and piRNA transcripts (5494 piRNAs) in the adult brain (Perera et al, 2019 ). In agreement with this observation, it was recently demonstrated that the piRNA pathway has a crucial role in maintaining the homeostasis and the fate of hippocampal NSCs (Gasperini et al, 2021 ). In particular, the expression of MILI and piRNAs was found to be enriched in NPCs of the postnatal mouse hippocampus, compared to their differentiated progeny, and piRNA functions were shown to be essential for neurogenesis.…”
Section: Piwi-interacting Rnas and Other Classes Of Sncrnassupporting
confidence: 62%
“…In particular, the expression of MILI and piRNAs was found to be enriched in NPCs of the postnatal mouse hippocampus, compared to their differentiated progeny, and piRNA functions were shown to be essential for neurogenesis. Moreover, inhibition of the piRNA pathway in adult NPCs leads to senescence-associated inflammation and an increase in reactive astrogliogenesis (Gasperini et al, 2021 ), a condition which has been linked to age-related impairment of neurogenesis and neurodegeneration.…”
Section: Piwi-interacting Rnas and Other Classes Of Sncrnasmentioning
confidence: 99%